Morphofunctional assessment of serotonergic signaling in zebrafish (Danio rerio) exposed to environmental concentrations of fluoxetine - Fagundes, Kainã Rocha Cabrera [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Unconscious consumption and economic forces have intensified the release of contaminants of emerging concern (CECs) into aquatic systems, generating global ecological and health challenges. Among CECs, antidepressants such as fluoxetine (FLX), a selective serotonin reuptake inhibitor (SSRI), are widely prescribed and frequently detected in the environment at concentrations ranging from 0.5 ng L-1 levels in surface waters to near 1,000 ng L⁻¹ near wastewater effluents. Once released, FLX interacts with conserved serotonergic pathways in non-target aquatic organisms (NTAOs), altering development, behavior, reproduction, and physiology. In zebrafish (Danio rerio), FLX exposure has been linked to oxidative stress, neurotoxicity, and gut-liver axis disruption. However, the enteric nervous system (ENS) remains poorly explored as an ecotoxicological target, especially in early life-stages and serotonergic subpopulations. This study aimed to evaluate the morphofunctional effects of environmentally relevant concentrations of FLX on serotonergic signaling and ENS integrity in different zebrafish life-stages. We integrated molecular, morphological, and behavioral analyses to characterize early neurodevelopmental alterations, long-term ENS dynamics, and systemic consequences on gut-liver homeostasis. By establishing the ENS and gut-liver axis as remarkable biomarkers, this research improved the understanding of antidepressant ecotoxicity and highlighted stage-dependent responses in aquatic organisms.

O consumo inconsciente e as forças econômicas intensificaram a liberação de contaminantes de preocupação emergente (CPEs) em sistemas aquáticos, gerando desafios ecológicos e de saúde globais. Entre os CPEs, antidepressivos como a fluoxetina (FLX), um inibidor seletivo da recaptação da serotonina (ISRS), são amplamente prescritos e frequentemente detectados no ambiente em concentrações que variam de 0,5 ng L-1 em águas superficiais a cerca de 1.000 ng L-1 perto de efluentes de águas residuais. Uma vez no ambiente, a FLX interage com vias serotoninérgicas conservadas em organismos aquáticos não alvo (OANAs), alterando o desenvolvimento, o comportamento, a reprodução e a fisiologia. No zebrafish (Danio rerio), nosso modelo AONAs, a exposição à FLX tem sido associada ao estresse oxidativo, à neurotoxicidade e à alteração do eixo intestino-fígado. No entanto, o sistema nervoso entérico (SNE) permanece pouco explorado como um alvo ecotoxicológico, especialmente em estágios iniciais da vida e em subpopulações serotoninérgicas. Este estudo teve como objetivo avaliaros efeitos morfofuncionais de concentrações ambientalmente relevantes de FLX na sinalização serotoninérgica e na integridade do SNE em diferentes estágios de vida do zebrafish. Integramos análises moleculares, morfológicas e comportamentais para caracterizar alterações neurodesenvolvimentais inciais, a dinâmica do SNE a longo prazo e as consequências sistêmicas na homeostase intestinal-hepática. Ao estabelecer o SNE e o eixo intestinal-hepático como biomarcadores notáveis, esta pesquisa aprimorou a compreensão da ecotoxicidade antidepressiva e destacou respostas dependentes do estágio em organismos aquáticos.
Avaliação morfofuncional da sinalização serotoninérgica em peixe-zebra (Danio rerio) exposto a concentrações ambientais de fluoxetina
Keywords: Morphology; Enteric Nervous System; Zebrafish; Emergent Contaminants; Gut-liver axis; Morfologia; Sistema nervoso entérico; Peixe-zebra; Contaminantes emergentes na água